Day of deception - Hagee, John. (Nashville, Tenn. : T. Nelson Publishers, 1997)
Hagee, founder and pastor of the Cornerstone Church in San Antonio, "calls the reader to discern truth from falsehood in these last days."
Includes bibliographical references (p.226-233).
Keywords: Christianity -- United States; United States -- Moral conditions